FIXEL: roadside assistance mobile application / Mohd Suffian Sulaiman, Zuraidah Derasit and Muhamad Fitri Afiq Azmi - Sulaiman, Mohd Suffian; Derasit, Zuraidah; Azmi, Muhamad Fitri Afiq (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Many drivers have experienced difficulties in obtaining assistance when their vehicle breaks down on the road. This challenging circumstance is extremely stressful since there are constraints to obtaining assistance, such as the service provider being too far away or the service provider's phone number being unavailable. The difficulty in deciding on a service provider is also due to the desire to meet several criteria, such as the lowest service price and the shortest distance from the service provider. It has become difficult for service providers to attract new customers when they are unfamiliar with the area. Typically, drivers will select the most popular service provider, which may be a long distance away from them. These issues inspired the creation of this initiative, which aims to aid drivers and service providers via a mobile platform. Map navigation, service provider suggestions based on certain criteria, online payment, and direct communication between drivers and service providers are all elements of the app. To improve the quality of choosing the proper service provider based on the criteria involved, such as service availability, costs, distances, and ratings, one of the multi-criteria decision-making methods was utilised. The proposed project's goal is to provide a communication platform for drivers and service providers, as well as a recommendation list of service providers who meet all of the criteria.